STRATEGI PEMBERDAYAAN KOMUNITAS PESISIR DALAM MENGELOLA PARIWISATA PANTAI MELALUI PENINGKATAN DAYA TARIK WISATA PANTAI DIKAWASAN TELUK TOMINI - Fachrussyah, Zc; Ahmad, Indra G.; Arman, Veggy; Lantu, Iin Susilawati (Jurnal Abdi Insani, 2025)
This article discusses a community service program integrated with the Community Service Program (KKN) in Torosiaje Village, Popayato District, Pohuwato Regency. The purpose of this program is to empower coastal communities in managing beach tourism through increasing tourist attractiveness. The method used in this program is Participatory Learning and Action (PLA). The stages of implementation are economic improvement through training activities on the use of social media and AI applications in the Information and Communication Technology RIRN by providing training and assistance to the community and youth organizations on how to use social media and AI applications in promoting and introducing Torosiaje village to the wider community. This program is expected to empower coastal communities in managing coastal tourism through increasing tourist attraction in Tomini Bay, especially in Torosiaje Village. Key word: Bajo Tribe, Tourism, Community Empowerment, Economy